Resisting multiple empires, cultivating transnational solidarity: a conversation among feminist-of-color scholar-activists - Li, Lin; Kazemi, Sona; Zheng, Wang; Lin, Yi-Chun Tricia (International Feminist Journal of Politics, 2025)
Keywords: China; Iran; Multiple empires; US feminism; dept.wgs; transnational solidarity

Transnational Indigenous feminisms: Four narratives for global Indigeneity - Lin, Y.-C.T.; Carlson, B.; Juanena, C.J.-A.; Sy, C.; Wilson, A. (Global networks of Indigeneity: Peoples, sovereignty and futures, 2023)
Keywords: dept.wgs

Selected Papers from the Seventh Annual Women's Studies Conference October 3-5, 1997 Latina Visions for Transforming the Americas/Perspectivas De La Mujer Latina En La Transformacion De Las Americas. - Women Studies Program (Women's studies program -- Southern Connecticut State University., 2000)
Keywords: Authors, Latin American; Congresses; dept.wgs; faculty_collection

A cry in the dark: The howls of wolves in horror and heavy metal music - Digioia, A. (Horror Studies, 2016)
Deranged howling is a hallmark of wolves, horror texts and heavy metal music artists. This article discusses how wolves, heavy metal music artists and horror text directors use diegetic sound to interact with listeners. Wolves use howls in real life to communicate their location and identity to their pack-mates. Howling in heavy metal music is used either as a literal sound or as a metaphor, to unite their audiences as one cohesive pack, or as a reunion call. The sound of a wolf in horror films indicates something wicked coming along, often in the form of a werewolf or other nefarious monsters. This article shows how a cry in the dark in horror texts, heavy metal music, and in the wilderness is a means of communicating an emotion or identity to a mass human or lupine audience. © 2016 Intellect Ltd Article.
Keywords: Diegetic sound; Heavy metal music; Horror; Howls; Wolves; dept.wgs

Lechery, lycanthropy and little red riding hood in type o negative’s ‘wolf moon (Including Zoanthropic Paranoia)’ - Digioia, A. (Metal Music Studies, 2016)
Type O Negative’s ‘Wolf Moon (including Zoanthropic Paranoia)’ seems to be a melodic ode to lascivious werewolves or to sexual intercourse during menstruation, which is transformative, allowing participation to channel animalistic instincts. Subject to more critical examination, ‘Wolf Moon (including Zoanthropic Paranoia)’ can also be presented as a contemporary incarnation of the ‘Little Red Riding Hood’ myth. Both contain the same themes: the stigmatization of eroticism, reclamation of agency, along with the nuances of gender identity and representation. Any Women’s Studies programme student is attuned to how storytelling and imagery of those within the story influence gender roles and their perceptions. Real-life themes are undoubtedly found within fairy tales as well, with a special emphasis on how women who do not remain in their proper place are punished because of it. In ‘Wolf Moon (including Zoanthropic Paranoia)’, the woman is rewarded for those experiences, by being permitted to indulge in her darkest desires. Meeting (or meating) a wolf that is hungry for you is nothing to fear in Type O Negative’s version of ‘Little Red Riding Hood’. Instead, it is the hallmark of a ‘great day’, and is something that should be celebrated. As ‘Little Red Riding Hood’ traverses onward throughout the western society’s cultural consciousness, one can only hope for further metal music acts interpretations of this infamous fairy tale. Representation matters, and the nuances of how the female gender has been portrayed throughout the centuries as reflected in the re-telling of a fairy tale is a subject that warrants a closer look through metal music and gender. © 2016 Intellect Ltd Article.
Keywords: Feminism; Gender; Little Red Riding Hood; Menstruation; Sexuality; Type O Negative; Wolves; dept.wgs